2011
DOI: 10.1086/660104
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity ofStriga hermonthicaPopulations in Ethiopia: Evaluating the Role of Geography and Host Specificity in Shaping Population Structure

Abstract: Striga hermonthica, a root hemiparasitic Orobanchaceae, severely constrains grain production in subSaharan Africa. Host specificity and geography may play important roles in shaping the population structure of S. hermonthica, with the Rift Valley potentially presenting a significant barrier to dispersal. Genetic diversity was assessed in 12 S. hermonthica populations from locations in Ethiopia. Of these, seven populations were parasitic on sorghum, two each on tef and maize, and one on finger millet. Genetic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 28 publications
5
26
0
Order By: Relevance
“…Some diversity assessment studies using allozymes and random amplified polymorphic DNA demonstrated that geographic distance played a major role in determining the genetic differentiation in S. hermonthica populations collected from different countries in the various regions of Africa (Bharathalakshmi et al, 1990; Kuiper et al, 1996; Koyama, 2000). Similar evidence was presented in another study that examined the genetic diversity among S. hermonthica collections from different regions in Ethiopia using amplified fragment length polymorphism (Welsh and Mohamed, 2011). The occurrence of such variable populations of S. hermonthica may elicit significant changes in reaction patterns of host genotypes from one region to another (Haussmann et al, 2001).…”
supporting
confidence: 75%
“…Some diversity assessment studies using allozymes and random amplified polymorphic DNA demonstrated that geographic distance played a major role in determining the genetic differentiation in S. hermonthica populations collected from different countries in the various regions of Africa (Bharathalakshmi et al, 1990; Kuiper et al, 1996; Koyama, 2000). Similar evidence was presented in another study that examined the genetic diversity among S. hermonthica collections from different regions in Ethiopia using amplified fragment length polymorphism (Welsh and Mohamed, 2011). The occurrence of such variable populations of S. hermonthica may elicit significant changes in reaction patterns of host genotypes from one region to another (Haussmann et al, 2001).…”
supporting
confidence: 75%
“…First, geographic location appears to play the greatest role in determining genetic differences between the two O. crenata accessions (with only 19% of the divergence occurring among the two faba bean or lentil grown O. crenata accessions). In the case of O. aegyptiaca , O. cumana and Striga hermonthica , genetic distance observed among populations is proportional to the geographical distance between the populations . However, conflicting results showed that there is no clear tendency in distribution of the genetic variability when considering geographical distance in O. crenata populations in Egypt, Spain or Israel as well as for O. hederea and O. ramosa in France …”
Section: Discussionmentioning
confidence: 99%
“…For example, witchweed (Striga hermonthica), a parasitic weed of cereal crops, has been shown to withstand a wide range of environmental conditions and can parasitize different hosts (Dawoud and Sauerborn, 1994;Ali et al, 2009). Based on AFLP (amplified fragment length polymorphism) markers, this genetically diverse outcrossing weed does not show genetic differentiation correlated with host specificity, but rather, it is correlated with geography (Welsh and Mohamed, 2011), suggesting that the weed is a generalist that can easily invade new crop hosts. Similarly, no genetic differentiation based on AFLP has been found between populations of broomrape (Orobanche foetida) infesting wild legumes and a population parasitizing cultivated vetch, suggesting a generalist ability to undergo host shifts onto cultivated species (Vaz Patto et al, 2008).…”
Section: The Origins Of Agricultural Weedsmentioning
confidence: 97%